Phytoremediation of Palm Oil Mill Effluent (POME) Using Water Lettuce and Duckweed - Dolhan, Mimi Malisa; Arbaan, Nur Shuhada; Bain, Noor Farahin (Tecno Scientifica Publishing, 2024)
Phytoremediation is a widely recent studied and applied technology, using various plants to remediate contaminants from wastewater by extraction, containment or destruction method which also known as eco-friendly and cost-effective techniques compared to conventional processes. The huge increased of palm oil production industry has become major environmental concern but not much have been said about the negative effects. Three major waste streams in processing palm oil were gaseous (pollutant gases), liquid (POME) and solid (palm press fibre, chaff, palm kernel shell and empty fruit bunch). The aim of this study was to determine the potential of water lettuce (Pistia stratiotes) and duckweed (Lemna minor) in removing contaminants in POME. Seven water quality parameters based on Sewage and Industrial Effluent Discharge Standards were selected in this study like pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammoniacal nitrogen (NH3-N), iron (Fe) and zinc (Zn). POME sample were placed in 3 basins for 28 days; (basin 1 – control, basin 2 – duckweed, Basin 3 – water lettuce), and each basin were tested with different retention time. The results showed that both studied plants have positive result as phytoremediation agents effectively in removing contaminants of POME. To achieve optimal contaminant reduction, incorporate a combination of phytoremediation and other complementary treatment would be beneficial before POME release into waterways.